Efficacy of sodium alginate as fat replacer on the processing and storage quality of buffalo mozzarella cheese. Issue 3 (8th May 2017) - Chatli, Manish Kumar; Gandhi, Neeraj; Singh, Parminder
Abstract : Purpose: The sensory quality and yield of mozzarella cheese deteriorate as the fat content in milk is reduced. This study aims to evaluate the efficacy of sodium alginate as a fat replacer in low-fat buffalo mozzarella cheese on the basis of processing and storage (4 ± 1°C) quality. Design/methodology/approach: Five treatments of buffalo mozzarella cheese, viz., control full-fat cheese (6.0 per cent milk fat; CFFC), control low-fat cheese (<0.5 per cent milk fat) without sodium alginate (CLFC), low-fat cheese with 0.1 per cent sodium alginate (LFC-1), 0.2 per cent sodium alginate (LFC-2) and 0.3 per cent sodium alginate (LFC-3), were comparatively evaluated. Findings: Increase in the level of sodium alginate increased the percent yield of treated low-fat cheese than CLFC. Addition of sodium alginate to low-fat cheese resulted in decrease in hardness ( p = 0.023) and chewiness than CLFC. Meltability was significantly decreased ( p = 0.03) in low-fat cheese than CFFC. It was recorded as 1.5 ± 0.14 cm for CFFC to 0.2 ± 0.08 cm in LFC-3. Sensory panellists awarded LFC-3 highest and lowest to LFC-1; however, treated products at all selected levels were superior to CLFC. Oxidative stability and microbial stability were improved in LFC-3 than CFFC during storage. Practical implications: Results concluded that 0.3 per cent sodium alginate is optimum for the development of extended shelf-life functional/low-fat/low-calorie buffalo mozzarella cheese. Originality/value: Processing interventions can be successfully used to develop low-fat/low-calorie mozzarella cheese with acceptable sensory attributes and longer storage life.